Analisis Kinerja Petugas Terminal Service Office Dalam Menjamin Kenyamanan Fasilitas Pelayanan Ruang Tunggu Penumpang Di Bandara Adi Soemarmo Surakarta - Reza Maulana Sultan; Suprapti Suprapti (Jurnal of Management and Social Sciences, 2024)
This research aims to find out: how regular monitoring of waiting room facilities by the terminal service officer unit is important to ensure that waiting room facilities are comfortable for passengers to use. If the terminal service office officers are negligent or do not adhere to the SOP guidelines in carrying out supervision, it can result in the functions of the waiting room facilities not being properly monitored so that when there are damaged facilities and so on they cannot be handled quickly which results in passengers experiencing problems. Disappointment This study used qualitative research methods. The data collection techniques used were observation, interviews, documents, and documentation along with observations. The researcher directly carried out observations, the researcher also explained the results of the data taken during the interviews and observations. For the interview, the researcher interviewed the terminal service office officers 3 sources with the document data obtained researcher from documentation of the activities of terminal service office officers when carrying out duties and responsibilities in the field and also in the form of implementation documents for the data analysis techniques used, namely data collection, data reduction, data presentation, discussion, and conclusions. The role of the performance of Terminal Service office officers in carrying out their duties and responsibilities to carry out operational activities for all facilities by the Standard Operational Procedures in the terminal service office By providing all facilities, especially in the departure and arrival areas, which makes service users feel satisfied. Obstacles faced by Terminal service office Based on the results of observations or field observations, it is the lack of personnel and lack of coordination with related units in carrying out operational activities which is the cause of the failure to fulfill the maximum performance of Terminal Service office officers to support security, comfort, smoothness, and safety of anyone at the airport.